SOSIALISASI JURNAL KEWIRAUSAHAAN DAN BISNIS UNTUK MENINGKATKAN PUBLIKASI PERGURUAN TINGGI - Susantiningrum Susantiningrum; Eddy Triharyanto; Dimar Hantari (Universitas Sebelas Maret, 2018)
Jurnal Kewiruasahaan dan Bisnis (JKB) is a journal published by PPKwu twice in a year. Currently the journal has a printed ISSN and an electronic ISSN. To enter the accredited journal stage, one of the provisions is that the articles published must consist of at least 2 different institutions. Starting in 2015, JKB has published a journal containing articles from two different institutions. However, there are still few articles from institutions other than the UNS. This is due to the absence of socialization of the Entrepreneurship and Business Journal to other institutions. This activity aims to socialize the Entrepreneurship and Business Journal to other institutions. Hoped that it will increase the number of article publications from UNS and other institutions, increase the number of peer reviewers of JKB, increase the branding index of PPKwu, improve the network of collaboration so that they can achieve the UNS mission, it is UNS towards world class university.